URGENSI PARTISIPASI GERAKAN SOSIAL MAHASISWA DALAM PENINGKATAN KUALITAS PEMILU 2024 - M. Hkikmat, Mahi (Jurnal Keadilan Pemilu, 2021)
The community in the whole world recognizes that the position of youth is very strategic. From the youth, born a group that is quantitatively small, but qualitatively very calculated. The character of youth is unique, energetic, idealistic, critical, and academic. In some event, youth became a driving force, even a battering ram, so that the history of the world, including the history of Indonesia, recorded the events of changes in civilization as a result of its terrible social movements. They are students. Therefore, in facing the General Election 2024, which is predicted to be more difcult and more complicated than the previous election, the government and election organizers should optimally involve the students. However, looking at their academic characteristics, students are more appropriate to be guardians for the realization of Direct, General, Free, Confidential (LUBER) and Honest and Fair (JURDIL) principles with the Election Supervisory Agency (BAWASLU), in order to combat political corruption and encourage double-minded democracy.